Lactiplantibacillus plantarum CR12 attenuates chronic unforeseeable mild stress induced anxiety and depression-like behaviors by modulating the gut microbiota-brain axis - Junxing Ma; Yaoxing Chen; Zixu Wang; Ran Wang; Yulan Dong (Journal of Functional Foods, 2023)
Depression is a progressive neurodegenerative disease characterized by cognitive deficits and psychiatric symptoms. The gut microbiota-brain axis plays a pivotal role during depression development. CUMS mice and CUMS + FLX mice were used in the study. Finally, Lactiplantibacillus plantarum (L. plantarum) CR12 powder group were orally administrated to mice with CUMS. We used Open field test, Morris water maze, Tail suspension test and Sucrose preference test to examine learning related behaviors. In addition, Immunofluorescence, ELISA, qPCR, Western blot and Microbial sequencing were employed to address Cognitive and behavioral disorders in CUMS mice. We found that treatment of L. plantarum CR12 significantly improved cognitive function and spatial memory of Open field test, Tail suspension test and Sucrose preference, accompanied by attenuated the anxiety- and obsessive-like behaviors in the CUMS depression mice model and increased hippocampal autophagy levels, decreased neurotransmitter levels. Notably, L. plantarum CR12 re-constructed the gut microbiota composition, including increasing the relative abundance of Lactobacillus and reducing the relative abundance of Helicobacter pylori (H. pylori), and enhanced the butyrate formation, as well as related microbes levels. In conclusion, the present study indicated that L. plantarum CR12 significantly attenuates the cognitive and mental deficits in the CUMS mice, which could be partly explained by the reshaped microbiome and enhanced SCFAs formation in the gut. L. plantarum, as a probiotics, can be translated into a novel microbiota-targeted approach for managing metabolic and neurodegenerative diseases.